2024
DOI: 10.1002/chem.202303681
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the Electrochemical Stability of N‐Heterocyclic Carbene Monolayers on Gold

Nathaniel L. Dominique,
Aruna Chandran,
Isabel M. Jensen
et al.

Abstract: N‐heterocyclic carbene (NHC) monolayers are transforming electrocatalysis and biosensor design via their increased performance and stability. Despite their increasing use in electrochemical systems, the integrity of the NHC monolayer during voltage perturbations remains largely unknown. Herein, we deploy surface‐enhanced Raman spectroscopy (SERS) to measure the stability of two model NHCs on gold in ambient conditions as a function of applied potential and under continuous voltammetric interrogation. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…The first publication, by Pellitero et al, 21 demonstrated that NHC monolayers can passivate gold electrodes to the same extent as benchmark thiol monolayers (see capacitive currents in Figure 3A, left vs right), and achieve comparable stability over 7 days of continuous voltage cycling (Figure 3B). Similar observations were made in a following publication by Dominique et al, 36 in which the stability of NHC monolayers on gold under continuous voltage cycling was investigated via surface-enhanced raman spectroscopy (SERS, Figure 3C). This second study demonstrates that NHC monolayers on gold can tolerate voltage modulation for over 11,000 cycles.…”
Section: ■ Strategies Based On Self-assemblysupporting
confidence: 82%
“…The first publication, by Pellitero et al, 21 demonstrated that NHC monolayers can passivate gold electrodes to the same extent as benchmark thiol monolayers (see capacitive currents in Figure 3A, left vs right), and achieve comparable stability over 7 days of continuous voltage cycling (Figure 3B). Similar observations were made in a following publication by Dominique et al, 36 in which the stability of NHC monolayers on gold under continuous voltage cycling was investigated via surface-enhanced raman spectroscopy (SERS, Figure 3C). This second study demonstrates that NHC monolayers on gold can tolerate voltage modulation for over 11,000 cycles.…”
Section: ■ Strategies Based On Self-assemblysupporting
confidence: 82%
“…19 Vibrational spectroscopies such as high-resolution electron energy loss spectroscopy (HREELS), 11,20 surface-enhanced Raman spectroscopy (SERS), 21,22 and reflection absorption infrared (IR) spectroscopy (RAIRS) 23,24 have been applied as a tool to study NHC SAMs. They are often used to monitor monolayer formation and stability, 24,25 surface chemical reactions, 26,27 and catalysis. 28,29 While previous studies have reported on a subset of the imidazolium and benzimidazolium NHC vibrational modes, 11,30 a systematic and rigorous vibrational mode analysis of NHCs bound to gold is missing in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Surface ligands play a key role in controlling not only the colloidal stability of metal nanoparticles (NPs) but also how NP cores function and/or interact with molecules and surroundings. , Adding polymer ligands to NPs, termed polymer grafted nanoparticles (PGNPs), is of particular interest, given the rich chemistry of polymers to design and tailor the surface properties of metal NPs. Among many examples, poly­(ethylene glycol) (PEG) grafted plasmonic NPs, e.g. , gold NPs (AuNPs), have received tremendous interest due to their biocompatibility and antifouling properties for applications like bioimaging and theranostics. In the “grafting to” approach, polymer ligands can replace the original capping ligands on presynthesized NPs while not changing their well-defined nanostructures. Thiol-terminated polymers have been extensively used in the modification of various metal NPs through the formation of metal–thiolate binding as the self-assembled monolayers. , In regard to AuNPs, Au-thiolate (Au–S) has a moderate binding energy of 126 kJ/mol as a semicovalent bond, , although it becomes dynamic at elevated temperatures. Other metal–organic bindings, such as N-heterocyclic carbenes (NHCs), have recently risen as promising alternatives to thiols due to the chemical stability of metal–C bonds against oxidants and heating. NHCs interact with AuNPs via Au–C binding with a binding energy of 158 kJ/mol . As a strong σ donor, NHCs have proven to be efficient in stabilizing NPs and tuning their selectivity in various catalytic reactions, e.g.…”
mentioning
confidence: 99%